Respuesta del cultivo de remolacha (Beta Vulgaris) a la aplicación de tres láminas de riego en el cantón Latacunga, provincia de Cotopaxi campus Salache, 2022 – 2023. - Tipán Zambrano, Alexander Eduardo (2023)
The project was carried out on the Salache campus, Latacunga canton, Cotopaxi Province, a study was carried out on the influence of the volume of water applied to the beet crop (beta bulgaris), where three types of irrigation sheets were applied with differences in 20 and 60% between them, 5 variables were determined (height, number of leaves, thickness, weight, volume of water) with which it determined what type of response the crop has to different volumes of water applied, the study was carried out in a 70-day cycle where with the help of the meteorological station (M1238) we proceeded to take evaporation and precipitation data, the applied irrigation sheets were maintained, data was taken from 2 variables (height and leaf number) every 15 days and the other three at the end of the cycle, the 100% ETc sheet was the one that showed the best results, giving a high mean in each of the variables, the sheet with 60% difference is the one with the lowest results, with a volume total of 7366 m3/ha in the entire cycle.